Perioperative management of gastrointestinal surgery in a resource-limited hospital in Niger: Cross-sectional study. (June 2020) - Adamou, Harissou; Amadou Magagi, Ibrahim; Adakal, Ousseini; Doutchi, Mahamadou; Habou, Oumarou; Boukari, Mamane; James Didier, Lassey; Sani, Rachid
Abstract: Background: Perioperative management in digestive surgery is a challenge in sub-Saharan Africa. Objective: To describe the process and outcomes of perioperative management in gastrointestinal surgery. Materials and methods: This was a single center cross-sectional study over a 4-month period from June 1 to September 30, 2017, in a Nigerien hospital (West Africa). This study included caregivers and patients operated on gastrointestinal surgery. Results: We collected data for 56 caregivers and 253 patients underwent gastrointestinal surgery. The average age of caregivers was 38.6 ± 8.7. The median length of professional practice was 9 years. Almost 52% of caregivers (n = 29) did not know the standards of perioperative care. The median age of patients was 24 years, and male gender constituted 70% of cases (n = 177) with a sex ratio of 2.32. Patients came from rural areas in 78.2% (n = 198). Emergency surgery accounted for 60% (n = 152). The most surgical procedure was digestive ostomies performed in 28.9% (n = 73), followed by hernia repair and appendectomy in 24.5% (n = 62) and 13.9% (n = 35) respectively. The postoperative course was complicated in 28.1% (n = 71) among which 13 deaths. In the group of caregivers, the poor practice of perioperative management was associated with poor professional qualification, insufficient equipment, insufficient motivation (p < 0.05). The ASA3&ASA4 score, undernutrition, emergency surgery, poor postoperative monitoring, and poor psychological preparation were associated with complicated postoperative outcomes (p < 0.05). Conclusion: The inadequacy of the technical platform and the lack of continuous training for healthcare staff represented the main dysfunctions of our hospital. The risk factors for complications found in this study need appropriate perioperative management to improve prognosis in gastrointestinal surgery. Highligth: Perioperative care in gastrointestinal surgery in a challenge in Sub-Saharan countries. This setting is characterised by the difficulty of geographical access to hospital, lack of equipment. Risk factors for complications are multifactorial. This study can be a draft for improvement the quality of care in low resource settings.